5-Phenyl-3-(2-thienyl)-1,2,4-triazolo[3,4-a]isoquinoline - Khan, F.N.; Manivel, P.; Prabakaran, K.; Hathwar, V.R.; Ng, S.W. (International Union of Crystallography, 2010)
In the title molecule, C(20)H(13)N(3)S, the triazoloisoquinoline ring system is approximately planar, with an r.m.s. deviation of 0.045 angstrom and a maximum deviation of 0.090 (2) angstrom from the mean plane for the triazole ring C atom which is bonded to the thiophene ring. The phenyl ring is twisted by 52.0 (1)degrees with respect to the mean plane of the triazoloisoquinoline ring system. The thiophene ring is rotationally disordered by approximately 180 degrees over two sites, the ratio of refined occupancies being 0.73 (1): 0.27 (1).